Digital Academic Supervision Model for Enhancing Instructional Leadership of Madrasah Principals: Development and Effectiveness of the ABDUL Application - Abdullah; Satori, Djam’an; Sururi; Suryadi; Ulfa, Maria (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Ineffective academic supervision management in madrasahs creates significant gaps between learning standards and practices, hindering instructional leadership of madrasah principals. This study developed a digital academic supervision model based on ABDUL—Digital Guidance Application for Outstanding Academic Supervision—integrating instructional leadership theory, transformative supervision theory, and management information systems theory to enhance the effectiveness of madrasah principals' instructional leadership. The research employed a Research and Development (R&D) approach over 12 months in three State Madrasah Aliyah in Bireuen Regency, Indonesia, involving 20 participants. Development followed six systematic stages: preliminary study, model design, expert validation, limited trial, revision, and effectiveness evaluation. Data were collected through multiple triangulation methods: semi-structured interviews, participatory observation, comprehensive documentation, expert validation instruments, and user response questionnaires. Expert validation confirmed 92.5% model feasibility (highly feasible) with 87% positive user responses (86.5% average satisfaction). Implementation demonstrated significant effectiveness, with a 27.7% increase in madrasah principals' managerial competence, a 24.6% improvement in teachers' professional competence, and a 36.5–45.8% enhancement in learning quality across five dimensions. The model transformed supervision culture from evaluative-punitive to empowering-collaborative approaches, with 85% of teachers experiencing perception change. This research presents a new conceptual framework that integrates three theoretical corpora within Islamic educational management contexts, offering both theoretical advancements and practically implementable blueprints for the digital transformation of academic supervision management in Indonesian Islamic schools.